2022
DOI: 10.1021/acscatal.1c04340
|View full text |Cite
|
Sign up to set email alerts
|

X-Type Aluminyl Ligands for Transition-Metal Catalysis

Abstract: Transition-metal complexes that bear group-13 X-type metalloligands have attracted considerable interest on account of their strong σ-donicity, which can dramatically tune the reactivity of transition-metal catalysts. Among the group-13 X-type metalloligands, X-type aluminyl ligands are especially interesting due to the low electronegativity and strong Lewis acidity of the Al atom. However, transition-metal complexes that bear X-type aluminyl ligands had until recently remained elusive. In this perspective, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 99 publications
0
17
0
Order By: Relevance
“…). Indeed, the TM-aluminyl complexes have shown their potential in small-molecule activation in recent studies, as exemplified by their insertion reactions with heteroallenes like carbon dioxide (CO 2 ) ( vide infra ). Because of the possible implication of TM-aluminyl complexes in catalysis, they have recently attracted increasing attention in the aspects of synthesis, reactivity, and electronic structure studies. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Indeed, the TM-aluminyl complexes have shown their potential in small-molecule activation in recent studies, as exemplified by their insertion reactions with heteroallenes like carbon dioxide (CO 2 ) ( vide infra ). Because of the possible implication of TM-aluminyl complexes in catalysis, they have recently attracted increasing attention in the aspects of synthesis, reactivity, and electronic structure studies. …”
Section: Introductionmentioning
confidence: 99%
“…Among those TM-aluminyl complexes reported to react with heteroallenes, there are simple structures with a clear TM–Al σ bond ,, and more sophisticated structures with extensive bridging across the TM center and the aluminyl unit. The focus of this study will be on the understanding of reactivity for those simpler cases with an unsupported TM–Al bond, in which there should be less influence from the other coordinations and it would allow us to pinpoint the source of reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…21 This provides a further example how heterobimetallic cooperativity can affect the reactivity or selectivity of a main group species. 22–24…”
mentioning
confidence: 99%
“…21 This provides a further example how heterobimetallic cooperativity can affect the reactivity or selectivity of a main group species. [22][23][24] Further variation of the substrate revealed that 1 can react selectively at sp 3 C-H bonds of pyridines in the presence of sp 2 C-H bonds. Hence, addition of 2-methylpyridine to 1 resulted in deprotonation of the CH 3 group to afford 7 in 495% NMR yield (Fig.…”
mentioning
confidence: 99%
“…21 This provides a further example how heterobimetallic cooperativity can affect the reactivity or selectivity of a main group species. [22][23][24] Further variation of the substrate revealed that 1 can react selectively at sp 3 C-H bonds of pyridines in the presence of sp 2 C-H bonds. Hence, addition of 2-methylpyridine to 1 resulted in deprotonation of the CH3 group to afford 7 in >95 % NMR yield (Figure 3).…”
mentioning
confidence: 99%